Expanding germ-organ theory: Understanding non-communicable diseases through enterobacterial translocation - Seenivasan Boopathi; P. Snega Priya; B. Haridevamuthu; S.P. Ramya Ranjan Nayak; Munisamy Chandrasekar; Jesu Arockiaraj; Ai-Qun Jia (Elsevier, 2023)
Diverse microbial communities colonize different habitats of the human body, including gut, oral cavity, nasal cavity and tissues. These microbial communities are known as human microbiome, plays a vital role in maintaining the health. However, changes in the composition and functions of human microbiome can result in chronic low-grade inflammation, which can damage the epithelial cells and allows pathogens and their toxic metabolites to translocate into other organs such as the liver, heart, and kidneys, causing metabolic inflammation. This dysbiosis of human microbiome has been directly linked to the onset of several non-communicable diseases. Recent metabolomics studies have revealed that pathogens produce several uraemic toxins. These metabolites can serve as inter-kingdom signals, entering the circulatory system and altering host metabolism, thereby aggravating a variety of diseases. Interestingly, Enterobacteriaceae, a critical member of Proteobacteria, has been commonly associated with several non-communicable diseases, and the abundance of this family has been positively correlated with uraemic toxin production. Hence, this review provides a comprehensive overview of Enterobacterial translocation and their metabolites role in non-communicable diseases. This understanding may lead to the identification of novel biomarkers for each metabolic disease as well as the development of novel therapeutic drugs.